1990
DOI: 10.1190/1.1442843
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of topography into two‐dimensional resistivity inversion

Abstract: Direct current resistivity data acquired on rough terrain can be interpreted by using an appropriate inversion technique after a topographic correction. In order to avoid the influence of a possibly incomplete topographic correction, an improved two-dimensional resistivity inversion algorithm has been developed to estimate the subsurface resistivity distribution in the presence of topography.In this paper, fully discretized modeling is based on the finite-element method, and the iterative inversion scheme is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 10 publications
0
42
0
1
Order By: Relevance
“…The forward part of the 2-D inversion program used in this study is based on the finite element method and the inverse part is based on the least-squares optimization technique (deGrootHedlin and Constable 1990;Tong and Yang 1990;Loke and Barker 1996) …”
Section: Methodsmentioning
confidence: 99%
“…The forward part of the 2-D inversion program used in this study is based on the finite element method and the inverse part is based on the least-squares optimization technique (deGrootHedlin and Constable 1990;Tong and Yang 1990;Loke and Barker 1996) …”
Section: Methodsmentioning
confidence: 99%
“…Contrary to relevant works of Fox et al (1980), Tong & Yang (1990) showed that previous normalisation techniques cannot completely take into account all non-linear effects. They showed also that the best way to remove non linear effects is to integrate explicitly the topography in the model.…”
Section: D + Inversion Strategymentioning
confidence: 79%
“…There is significant topography along the survey line. The topography was incorporated into the inversion model using a distorted finiteelement grid such that the surface of the grid matches the actual topography (Tong and Yang, 1990;Silvester and Ferrari, 1990;Sasaki et al, 1992). The distribution of the model cells were initially made using the same method as for a model without topography.…”
Section: Rock Quality Survey Swedenmentioning
confidence: 99%